Technical Debt in Brazilian Software Startups: Perceptions of Professionals in Paraná - Santos, Adauto; Kuspil, Jonathan; Rando, Deverson; Santos, Dionnes; Leal, Gislaine Camila; Balancieri, Renato; Oliveirajr, Edson (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
Technical Debt (TD) can be described as a software solution quickly applied to temporarily solve a problem encountered, but which may have negative consequences for the product in the future, being a common practice in organizations. Due to the intrinsic characteristics of startups, innovation, and agility may be more affected by TD. This paper aims to understand how software practitioners in northern Paraná Brazil, perceive the concept of TD, what its main types are, ways of coping and how it is documented. For this, a survey was carried out with software practitioners in startups. Based on the answers obtained, it was observed that 72% of the participants consider having low familiarity with the subject, although 60% consider that TDs have a high impact on software products. The absence of test case development, documentation, and bad practices were the most common types of TD found in this study. Still, the main aspects for prioritizing the resolution of TDs were the impact, severity, and customer demands.